Making and breaking gender inequalities in work - Mia Rönnmar; Susan Hayter (Making and breaking gender inequalities in work, 2024)
"This timely book expertly analyses the persistence of gender inequalities in work. Despite the progress made through frameworks regulating work and employment relations, the COVID-19 pandemic exposed and exacerbated gender divides in labour markets. The authors present innovative ways to promote gender equality in a variety of industrial relations systems, welfare state models and labour market sectors. Making and Breaking Gender Inequalities in Work offers a rich, global and comparative study of this critical topic, addressing developments in formal and informal economies in countries with different levels of economic development. Mia Rönnmar and Susan Hayter have carefully selected expert contributors who apply an interdisciplinary approach and combine a range of theories and methodologies to provide fresh insights on the implications of the COVID-19 pandemic, and on how to tackle gender inequalities in areas such as work-life balance, equality law, global value chains and collective bargaining. Illustrating the key issues in the subject, this book is an excellent resource for academic researchers and scholars in the fields of industrial relations, work and employment relations, gender studies and equality, labour and international law. Policymakers and employers' and workers' organizations at the national, regional and international levels will also find the analysis informative and enlightening"–
10.4337/9781035337477; 10.4337/9781035337477